Deriving Manageable Transdisciplinary Research Models for Complicated Problematics Associated with Next-Generation Cyber-Physical Systems - Horvath, Imre (Transdisciplinary journal of engineering & science, 2025)
As a continuation of the work previously published in two papers in this journal, this paper addresses the problem of systematically constructing sharable transdisciplinary research models (TRMs) for definitive research problematics (DRPs). The paper discusses the underpinning fundamentals and proposes a practical methodics that is underpinned by intuitive reasoning rather than by proven theories but relies on a lucid procedural framework. The main activities are discussed through a demonstrative example designated as ‘avoidance of frequent vehicle accidents at suburban road crossings'. First, a concise overview of the literature related to research models is provided and the work reported in this paper is placed in this context. Then, the operational aspects of the transdisciplinary research model development methodics are discussed. As a starting point, the proposed methodics assumes the availability of a comprehensive specification of the DRP. The conversion process includes six steps: (i) exploring research concepts by content analysis of the DRP, (ii) finding pertinent research concepts and combining them into a semantic map, (iii) selecting the most influential concepts and relations for parameterization, (iv) choosing multi-view research concept descriptor constructs and parameters (indicators, variables, and constants) for study, (v) creating sharable multi-modal representations of the research model, and (vi) external validation of the content by researchers and stakeholders. An adapted version of the validation square approach is used in then last assessment. The approved TRM is the starting point of the development of supradisciplinary research designs – this is however not addressed here due to page limitations.